2019
DOI: 10.1111/rda.13435
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of curcumin on lipopolysaccharide‐ and/or flagellin‐induced production of prostaglandin E2 and relative expression of proinflammatory cytokines in the primary bubaline endometrial stromal cells

Abstract: Contents Developing alternate therapies for bovine endometritis is important in the context of drug residues in the milk and emergence of antimicrobial resistant bacteria. In this regard, we studied the immunomodulatory effect of curcumin 30 µM, on lipopolysaccharide‐ (LPS) and/or flagellin (100 ng/ml each)‐induced prostaglandin E2 (PGE2) and proinflammatory cytokines (PIC) using primary bubaline endometrial stromal cells. After 24 hr treatment, the supernatant was assayed for PGE2 while cells were used for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Targowski ( 79 ) found that an intrauterine infusion of 100 g E. coli LPS increased the number of PMNs found in uterine secretions at 6 and 24 h after treatment in healthy cows. Rashid Dar et al ( 7 ) evaluated the immunomodulatory effect of curcumin 30 M, lipopolysaccharide (LPS), and/or flagellin (100 ng/mL each) on prostaglandin E2 (PGE2) and proinflammatory cytokines (PIC) production using primary bubaline endometrial stromal cells. They discovered that LPS stimulates PGE2 production strongly, but flagellin has a lesser stimulatory impact.…”
Section: Economic Consequences Of Immunoinfertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Targowski ( 79 ) found that an intrauterine infusion of 100 g E. coli LPS increased the number of PMNs found in uterine secretions at 6 and 24 h after treatment in healthy cows. Rashid Dar et al ( 7 ) evaluated the immunomodulatory effect of curcumin 30 M, lipopolysaccharide (LPS), and/or flagellin (100 ng/mL each) on prostaglandin E2 (PGE2) and proinflammatory cytokines (PIC) production using primary bubaline endometrial stromal cells. They discovered that LPS stimulates PGE2 production strongly, but flagellin has a lesser stimulatory impact.…”
Section: Economic Consequences Of Immunoinfertilitymentioning
confidence: 99%
“…Antibiotics administered intrauterine reduce uterine leukocytic activity, which could have major consequences in the treatment of metritis if the bacteria involved grow resistant to the antibiotic. Extensive use of antibiotics not only causes antimicrobial drug resistance but is also responsible for the secretion of drug residues in the milk (7). Apart from antibiotics, endometrial necrosis and fibrosis can be caused by overdose or continuous use of a variety of different drugs, such as Lugol's iodine and polyvinylpyrrolidone-iodine (66)(67)(68).…”
Section: Immunomodulators As a Replacement Therapeutic For Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation